Strategic Formulation for Small Business Development - Aganti, Auda; Diah Indriani, Mia Tantri (Journal of Business and Management, 2014)
Every business journey, heve to face certain condition to be able to get into the seattlement stage and became a sustainable business. For small business, there are a lot more obstacle to obtained the sustainable business. Due to the lack of resources, and a minimal operational system make the small business sometimes not be able to move into the next stage and potentially cause a bankrupcy if they can not overcome the obstacle. Problem in Soto Bening Bu Anik is used as the case study of this research. The root cause analysis showed that the main problem were : the business can not move into the next stage of the business growth and development., due to the lack of operation and managerial system in the business. The possible solution that have been made are : apply the corporate and functional strategies to be implement in the original store, and prepare for opening the new branch to increase the sales. Purposed solutions were examined through analysis based on internal and external situation of the business which combined the STP and SWOT analysis compare to the competitor analysis.Keywords: Small Business Development, Small Business Growth, Culinary Industry, Strategic Management